Clarification of the characteristics of needle-tip movement during vacuum venipuncture to improve safety - Fujii, Chieko (Vascular Health and Risk Management, 2013)
Complications resulting from venipuncture include vein and nerve damage, hematoma, and neuropathic pain. Although the basic procedures are understood, few analyses of actual data exist. It is important to improve the safety standards of this technique during venipuncture. This study aimed to obtain data on actual needle movement during vacuum venipuncture in order to develop appropriate educational procedures. Six experienced nurses were recruited to collect blood samples from 64 subjects. These procedures were recorded using a digital camera. Software was then used to track and analyze motion without the use of a marker in order to maintain the sterility of the needle. Movement along the X- and Y-axes during blood sampling was examined. Approximately 2.5 cm of the needle was inserted into the body, of which 6 mm resulted from advancing or moving the needle following puncture. The mean calculated puncture angle was 15.2°. Given the hazards posed by attaching and removing the blood collection tube, as well as by manipulating the needle to fix its position, the needle became unstable whether it was fixed or not fixed. This study examined venipuncture procedures and showed that the method was influenced by increased needle movement. Focusing on skills for puncturing the skin, inserting the needle into the vein, and changing hands while being conscious of needle-tip stability may be essential for improving the safety of venipuncture.